Quirky, jerky, extra-perky : more about adjectives - Cleary, Brian P., 1959-; Gable, Brian, 1949- (Minneapolis : Millbrook Press, 2007)
Illustrated verse explores the concept of adjectives and introduces many examples.
3.7
3-6
Keywords: English language -- Adjective -- Juvenile literature; English language -- Adjective; English language -- Parts of speech